Recent Wage Deceleration in Canada: Short-Run Response or Structural Change? - Kumar, Pradeep (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1987)
The paper reviews recent wage trends and patterns, and examines whether the wage deceleration since 1982 can be explained by the steady decline in inflation and the persistent high rates of unemployment.